(3CeGdj GHf GdTLQjs - (3GHf GdTLQj , gHI Gddg Hf Ydj Hf eMeO GdMSfj, CHh GdSYGOGJ,J (B542 (3g` s ((3HNW eDdagG s)
(3ChdgG (B:s
(3GdeLdS GdSGOS hGdNeShf jJVef eSGFd GdJQNje heG jJUd HgG heG de JSJYedg GdYQH EdG aj GdfOGA cfJ MOOJ GdePgH GdeNJGQ ef ePgHj GdJQNje s
(3BNQgG (B:s
(3ef GdeLdS GdKGdK hGdKeGfjf abGd YGHfj CQGPd GdfGS aefge ef QeGfj HYjH gh ajg hgh GdCHfI hGfbdH bhdg Ydjg aCUGH CSJg HGdYjH GdPj QeGfj Hg Cj GdPjf Qehfj ef gPjf GdUfajf hHgPjf GdhUajf s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JUMjMGJs
(3ef fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGAs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs